2018
DOI: 10.14419/ijet.v7i4.35.23078
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Framework of Critical Success Factors on Information Technology Project Management During Project Planning

Abstract: Organizations have made significant investments in ICT projects, hoping to gain competitive advantages, growth and improvement of productivity. The success and failures of the project is one of the fields in Project Management with most frequently discussed. Project planning is an important part in the project management and has a stronger impact on project success. However, weakness in project strategy and planning lead to lack of business support, inefficient use of resources, poor estimates, poor scope cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…), (2) Information quality (Accuracy, Consistency, Relevance, Availability, etc. ), ( 3 Other studies performed in the discipline of project management have shown the influence of some factors on project success such as Top management aid and support (Ullah, 2020), Project managers emotional intelligence and leadership competencies (Maqbool et al, 2017), Risk management practices (Pimchangthong and Boonjing, 2017), IT governance practices , Project sustainability management (Carvalho and Rabechini, 2017), Project planning (Adzmi and Hassan, 2018), Knowledge management processes (Conger, 2013;Yang et al, 2012) and Project Management Office (De Lucca et al, 2020;Pontes, 2020): RQ2: What are the factors that impact the especially the success of ICT4D initiatives?…”
Section: Resultsmentioning
confidence: 99%
“…), (2) Information quality (Accuracy, Consistency, Relevance, Availability, etc. ), ( 3 Other studies performed in the discipline of project management have shown the influence of some factors on project success such as Top management aid and support (Ullah, 2020), Project managers emotional intelligence and leadership competencies (Maqbool et al, 2017), Risk management practices (Pimchangthong and Boonjing, 2017), IT governance practices , Project sustainability management (Carvalho and Rabechini, 2017), Project planning (Adzmi and Hassan, 2018), Knowledge management processes (Conger, 2013;Yang et al, 2012) and Project Management Office (De Lucca et al, 2020;Pontes, 2020): RQ2: What are the factors that impact the especially the success of ICT4D initiatives?…”
Section: Resultsmentioning
confidence: 99%
“…In the work of Adzmi et al [ 29 ], focused on the Malaysian public sector, the following success factors were identified: involvement of functional department in planning; involvement of the client in planning; authority of project managers; monitoring and feedback; client consultation; communication; monitoring and feedback; experience of the project manager; planning effort; team member experience; team member commitment; customer involvement; priorities of the project by team leader; training; project manager appropriate assignment; project manager involved in the planning stage; communication among project manager and organizations; project mission; support of top management; project schedule/plans; client agreement; a well-defined scope; all resource were defined; usage of WBS; usage of Gantt Chart; usage of CPM; usage of project management software; technical tasks; troubleshooting; and level and effectiveness planning. The factors were classified into five categories: project management; project manager; organization competence; and method and techniques.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, the types of studies on CSFs in IT project management found are mainly of two types: literature review studies [ 27 , 29 , 30 ], which seek to identify which CSFs are most important; and surveys [ 28 , 31 – 33 ], which seek to find out which CSFs are most important to the success of the project according to the participants in the study, which generally include IT project managers and other top managers in the organizations. In the results section, a summary is made of the CSFs, from the last five years, found in the review of literature carried out.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of top management on the project has been studied by scholars globally. Based on the studies done by Busari et al (2019), Adzmi and Hassan (2018), Ahimbisibwe et al (2017), Yaghoobi (2018), Gingnell et al (2014), Remus and Wiener (2009), and Gelbard and Carmeli (2009 have positively correlated the top management role to the project success, however, in this study, it has been revealed that the top management role is not necessarily correlated positively to the success of the project, it can also be negatively correlated to project success, which can lead to ICT project cost overrun. This is especially during the RFP stage, where unrealistic theoretical commitments are made as instructed by the top management to secure the project.…”
Section: Comparison Of These Findings Against Previous Studiesmentioning
confidence: 99%